(3LhGeY cJGH LGdjfhS aj GdCOhjI GdeaQOIs - (3LGdjfhSs
(3ChdgG (B:s
(3bGd(B: (3GdCOhjI CQHYI CLfGS(B: (3aefgG eG dGjbhi GdHOf cPdc agh ef LfS GdGOhjI GdbJGdI s
(3BNQgG (B:s
(3hebOGQ GdCTQHI hcd hGMO efgG ai LOhd , HjfG ajg gPg GdCHhGH, hGfG eYJRe Pdc Ef TGA Gddg hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B175 - (3U(B178s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B77 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(3/2071) s
Keywords: (3GdWHs